Comparative analysis of password cracking tools / Ahmad Syahir Amzar Zulkafli - Zulkafli, Ahmad Syahir Amzar (College of Computing, Informatics, and Mathematics, 2024)
This comparative analysis aims to evaluate and compare various password cracking tools that are available in the market to provide an insight of its effectiveness, capabilities, and efficiency as well as provide a clear guideline of the best way on how to mitigate the risk from being the victim of password attack. The research methodology involves testing and analysing most famous password cracking tools which as John the Ripper, Hashcat, WPScan, and Hydra. The tools will be evaluated based on its performance, success rate, etc. Other than that, this project will also performing a wide variety of password attacking method such as brute force, rule based, and etc to assess their performance and effectiveness of each tool. Overall, this comparative analysis seeks to give a comprehensive understanding of password cracking tools which can be contribute to the field of cybersecurity by identifying the most effective tools and technique. In the end, a complete guideline on the best password practices can be used to avoid from any threat from password attack.